This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let us rewrite the summation in consideration as follows:
k = 0 ∑ ∞ a r c t a n ( 4 k 2 + 3 4 ) = a r c t a n ( 3 4 ) + k = 1 ∑ ∞ a r c t a n ( 4 k 2 + 3 4 )
We could manipulate the RHS as follows:
= a r c t a n ( 3 4 ) + k = 1 ∑ ∞ a r c t a n ( k 2 + 4 3 1 )
= a r c t a n ( 3 4 ) + k = 1 ∑ ∞ a r c t a n ( k 2 − 4 1 + 1 1 )
= a r c t a n ( 3 4 ) + k = 1 ∑ ∞ a r c t a n ( [ k − 2 1 ] [ k + 2 1 ] + 1 1 )
= a r c t a n ( 3 4 ) + k = 1 ∑ ∞ a r c t a n ( [ k − 2 1 ] [ k + 2 1 ] + 1 [ k + 2 1 ] − [ k − 2 1 ] )
We can now use the sum/difference identity for arctangents, which is as follows:
a r c t a n ( A ) − a r c t a n ( B ) = a r c t a n ( 1 + A B A − B )
Since we have A = k + 2 1 and B = k − 2 1 , we further simplify the RHS as
= a r c t a n ( 3 4 ) + k = 1 ∑ ∞ [ a r c t a n ( k + 2 1 ) − a r c t a n ( k − 2 1 ) ]
which, when evaluated, turns out to be a telescoping series.
This will further lead us to
= a r c t a n ( 3 4 ) + 2 π − a r c t a n ( 2 1 )
≈ 2 . 0 3 4 4 4
Thus giving us the answer to our question, 2 0 3 4 .